Communist Party in the Power System of the USSR - A. Ya. LIVSHIN (Контуры глобальных трансформаций: политика, экономика, право, 2018)
In this article major mechanisms and different stages of the  Bolshevik party’s transformation into a “party-state” are examined.  The Communist party has been brought to the surface of political life and power by the Russian revolution; the organizational  principles of the Party along with its approaches to political process  have to a larger extent evolved as results of the revolution.  Therefore the system of power which has reached its peak during  Stalin’s rule has both been the product of continuity as well as  change of the Russian political tradition. The Communist ideology  has served as main instrument of communication between the  authorities and the people. The Party occupied central position in  that system of communication; one of the most important tools of  the Party’s control over the Soviet society was propaganda. However the process of the communist regime acquiring legitimacy  has been rather lengthy; it was completed only by the late 1920s.  The basic principles of “unity” within a ruling group were rejected  when rivalry for power ended in Stalin’s favor. The central element in  the Communist party’s system of power was the ruling  elite – nomenclature. During World War II the institution of “party- state” has reached the highest degree of centralization; but  on the other hand, the decision-making system was rather flexible and adaptable as compared with the previous period. After  the War even within Stalin’s dictatorship the contours of oligarchic “collective leadership” were emerging. N. Khrushchev used  the same instrument as Stalin did – control over the Party apparatus – while consolidating his power. One of the important  results of Khrushchev’s rule was the institutionalization of the ruling  bureaucracy. Maintaining “stability” became the slogan for the new  stage of the Communist regime’s evolution. Socio- economic system  was getting increasingly complex and less manageable; different hierarchies, including local and industrial elites, have been failing to  make timely and correct decisions due to their rigidness and  sluggishness. The Party was attempting to compensate those  deficiencies, but was less and less capable of doing so. Gorbachev’s “Perestroika” which was based on the idea of democratic socialism  has finally ended the rule of the “party-state”. Having lost its internal  integrity the system of power has rapidly deteriorated.